1975
DOI: 10.1073/pnas.72.7.2706
|View full text |Cite
|
Sign up to set email alerts
|

Microfibril assembly by granules of chitin synthetase.

Abstract: Purified preparations of chitin synthetase (EC 2.4.1.16; UDP-2-acetamido2-eoxy--glucose:chitin 4-flacetamidodeoxyglucosyltransferase), capable of forming microfibrils in vitro, were isolated from yeast cells of Mucor rouxii. Chitin synthetase was obtained either by substrateinduced liberation of bound enzyme (54,000 X g pellet) or by isolation of unbound enzyme present in the 54,000 X g su ernatant of a cell-free extract. Both preparations contained ellipsoidal granules from about 350 to 1000 A diameter. Many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(24 citation statements)
references
References 15 publications
3
21
0
Order By: Relevance
“…The presence of such an inactive enzyme has also been demonstrated in 54000g supernatants from cell-free extracts from yeast cells of Mucor rouxii, where it was associated with identifiable particles called chitosomes (Ruiz-Herrera et al, 1975;Bracker et al, 1976). The role of these chitosomes in chitin synthesis has not yet been elucidated but it was suggested that they are extruded through the plasma membrane…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of such an inactive enzyme has also been demonstrated in 54000g supernatants from cell-free extracts from yeast cells of Mucor rouxii, where it was associated with identifiable particles called chitosomes (Ruiz-Herrera et al, 1975;Bracker et al, 1976). The role of these chitosomes in chitin synthesis has not yet been elucidated but it was suggested that they are extruded through the plasma membrane…”
Section: Discussionmentioning
confidence: 99%
“…by incubating these preparations with the substrate uridine-5'-diphospho-N-acetyl-~-glucosamine (UDP-GlcNAc) and the activator N-acetylglucosamine (GlcNAc) at 0 "C (Ruiz-Herrera & Bartnicki-Garcia, 1974 ;Ruiz-Herrera et al, 1975).…”
Section: A V E R M E U L E N M B J M R a E V E N A N D J Gmentioning
confidence: 99%
“…In N. crassa, the phosphatase PP1 (NCU00043), with a potential role in dephosphorylation of CHS-4 and another protein of potentially great interest, the serine protease p2, were identified in co-immunoprecipitations of CHS-4 and CHS-5. It was previously described that CHSs are zymogen proteins, which need to be activated proteolytically (Cabib and Farkas, 1971;Duran and Cabib, 1978;Leal-Morales et al, 1988;McMurrough and BartnickiGarcía, 1971;Ruiz-Herrera et al, 1975). Previous studies in N. crassa have shown that the total activity of CHSs requires trypsin as proteolytic activator (Arroyo-Begovich and Ruiz-Herrera, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the preincubation of chitin synthase with Rennilase and polyene prior to the addition of the substrate was 20 min.The reaction time was 1 hr and the temperature was 220C. The radioactive chitin formed was determined by a filtration method (5,16). The reaction rate (in the absence of polyene) was constant for at least 90 min, even with the most active preparations.…”
Section: Methodsmentioning
confidence: 99%